A metamaterial-free fluid-flow cloak - Tay, Fuyang (2023)
The model of ideal fluid flow around a cylindrical obstacle exhibits a long-established physical picture, where originally straight streamlines are deflected over the whole space by the obstacle. Inspired by transformation optics and metamaterials, recent theories have proposed the concept of fluid cloaking, which is able to recover the straight streamlines, as if the obstacle did not exist. However, such a cloak, similar to all previous transformation-optics-based devices, relies on complex metamaterials with inhomogeneous parameters and is difficult to implement. Here we deploy the theory of scattering cancellation and report on the experimental realization of a fluid-flow cloak without metamaterials. This cloak is realized by engineering the geometry of the fluid channel, which effectively cancels the dipole-like scattering of the obstacle. The cloaking effect is demonstrated through the direct observation of recovered straight streamlines in the fluid flow. Our work sheds new light on conventional fluid control and may find application in microfluidic devices.